A simple and mild acylation of alcohols, phenols, amines, and thiols with a reusable heteropoly acid catalyst (H6P2W18O62·24 H2O) - Romanelli, Gustavo Pablo (2008)
The acylation of alcohols, phenols, thiols, and amines with varied substitution using acid anhydrides is efficiently catalyzed by Wells-Dawson heteropoly acid (H6P2W18O62·24 H2O). Reactions proceed with very good to excellent yield in air at room temperature, using toluene as solvent (40 examples). The bulk catalyst was easily reused without appreciable loss of its activity.